Du manioc plus sain, des cultivateurs plus riches? - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1999)
L'Organisation nationale de recherche agricole (NARO), en Ouganda, a mis au point une variété de manioc résistante